Des Formes sonores en mouvement : Le Langage poétique de Stéphane Mallarmé - Pasini, Lucia (Rivista Italiana di Filosofia del Linguaggio, 2020)
Sonically moving forms» are the substance of music according to Hanslick, but this formula can also be applied successfully to metrically organized poetic lines, and in particular to the poems of Mallarmé. In order to examine this parallelism exhaustively, it is necessary to define the position of musical language in relation to its verbal counterpart, and to establish the status of musical processes such as meter and rhyme, which are commonly employed in poetic writing. Then, in Mallarmé’s specific case, it is demonstrated that he removes from his texts both the referentiality that verbal language ordinarily possesses, and his own authorial instance, in a process that accentuates the sound quality of the words. In this context, these words themselves come to meaning in a musical way, in three different fashions: firstly, once the Weltbezug is abolished, what remains of the words is their sound; secondly, this sound is organized according to musical phenomena, e.g. meter and rhyme; and finally, the imaginative construction of meaning is based on the mutual relationships that are established between words within the internal structure of the text. This is extremely interesting in the context of an inquiry about words and music: these different modes of interaction between the two languages constantly hold to account any theoretical proposition on the matter at hand because of their nature of historical occurrences.